Transperineal prostate biopsies for diagnosis of prostate cancer are well tolerated: a prospective study using patient-reported outcome measures - Wadhwa, Karan (Asian J Androl, 2017)
We aimed to determine short-term patient-reported outcomes in men having general anesthetic transperineal (TP) prostate biopsies. A prospective cohort study was performed in men having a diagnostic TP biopsy. This was done using a validated and adapted questionnaire immediately post-biopsy and at follow-up of between 7 and 14 days across three tertiary referral hospitals with a response rate of 51.6%. Immediately after biopsy 43/201 (21.4%) of men felt light-headed, syncopal, or suffered syncope. Fifty-three percent of men felt discomfort after biopsy (with 95% scoring <5 in a 0–10 scale). Twelve out of 196 men (6.1%) felt pain immediately after the procedure. Despite a high incidence of symptoms (e.g., up to 75% had some hematuria, 47% suffered some pain), it was not a moderate or serious problem for most, apart from hemoejaculate which 31 men suffered. Eleven men needed catheterization (5.5%). There were no inpatient admissions due to complications (hematuria, sepsis). On repeat questioning at a later time point, only 25/199 (12.6%) of men said repeat biopsy would be a significant problem despite a significant and marked reduction in erectile function after the procedure. From this study, we conclude that TP biopsy is well tolerated with similar side effect profiles and attitudes of men to repeat biopsy to men having TRUS biopsies. These data allow informed counseling of men prior to TP biopsy and a benchmark for tolerability with local anesthetic TP biopsies being developed for clinical use.